Co-creating real-world research skills - Prescott, Julie; Cross, Duncan; iliff, Pippa (International Journal for Students as Partners, 2020)
This case study considers a students-as-partners’ research project that aimed to develop technologically-driven tools to enhance teaching and learning in higher education. It focuses on how the project enabled student participants to gain real world research skills and experience. We present reflections from both a student and a staff perspective and propose START (Support, Time, Adapt, Risks, Trust) as an approach to engage students to gain real-world research skills. Support refers to providing support for skills gaps and learning in an applied setting. Time refers to providing time to settle into the project and develop confidence, including realistic timeframes and deadlines. Adapt refers to giving students the space to develop not only the required skills but also the tools to develop their own abilities and confidence through a supportive, flexible and open environment. Risks refers to taking risks for example in terms of roles, responsibilities and leadership. Trust refers to providing guidance and encouragement that will allow students to achieve on their own and take shared ownership.